2016
DOI: 10.1016/j.wasman.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia emissions from an anaerobic digestion plant estimated using atmospheric measurements and dispersion modelling

Abstract: Anaerobic digestion (AD) is becoming increasingly implemented within organic waste treatment operations. The storage and processing of large volumes of organic wastes through AD has been identified as a significant source of ammonia (NH3) emissions, however the totality of ammonia emissions from an AD plant have not been previously quantified. The emissions from an AD plant processing food waste were estimated through integrating ambient NH3 concentration measurements, atmospheric dispersion modelling, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The 'low' height corresponded to the height of the advanced filter surface, while the 'high' height was set at 1.5 m above the filter surface. These positions were selected based on previous research that measured NH3 emissions both from storage facilities and fields (Carozzi et al, 2013;Bell et al, 2016;Ferrara et al, 2016).…”
Section: Ammonia Emission Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'low' height corresponded to the height of the advanced filter surface, while the 'high' height was set at 1.5 m above the filter surface. These positions were selected based on previous research that measured NH3 emissions both from storage facilities and fields (Carozzi et al, 2013;Bell et al, 2016;Ferrara et al, 2016).…”
Section: Ammonia Emission Monitoringmentioning
confidence: 99%
“…Some studies have already assessed the impact of some processes, such as digestate storage or digestate spreading; however, little research has been conducted on the digestate separation process. The advanced filtration step required for fertigation using digestate has not yet been investigated (Wolf et al, 2014;Bell et al, 2016;Riva et al, 2016;Finzi et al, 2019). Since digestate filtration involves digestate movement in semi-open environments, it is important to evaluate potential emissions that may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it has been claimed that anaerobic digesters may exacerbate pollution rather than reduce it (Bell et al 2016; Friends of the Earth 2018c; Source Material 2018). It was calculated that the net additional ammonia emissions from them would be around 696,740 kg (Friends of the Earth 2018b), thus, questioning the effectiveness of AD in reducing animal waste from farming intensification.…”
Section: Northern Ireland: Backgroundmentioning
confidence: 99%
“…9 To question the potential of AD for mitigating environmental harms in farming even further, the government officials in Northern Ireland suggested that AD 'does not address the fundamental issue of excess nutrients in the manure, as it requires land spreading of the digestate' (DAERA 2014: 19). Therefore, there is a possibility that AD plants, while creating renewable energy, may increase ammonia emissions in Northern Ireland, primarily through the storage of feedstock and digestate, and the land spreading of the latter (Bell et al 2016).…”
Section: Anaerobic Digestion Subsidies and Environmental Harmmentioning
confidence: 99%
“…The emissions from IC-engine electricity generation process was based on the historic source test results [16], the emissions from micro-turbine generator wass based on [15]. When food waste is exposed to the air, it will produce toxic gases such as NH 3 and H 2 S [17,18]. The data of gas emissions happened in pretreatment and S-L treatment were from the environmental impact announcement of referenced food waste treatment project which was released by Zhejiang Industrial Environmental Design Institute Co. Ltd.…”
Section: Emissions Datamentioning
confidence: 99%